سمات الشخصية وعلاقتها بمعنى الحياة و التدفق النفسي لدى المصورين الفوتوغرافيين - قرنينة سعاد (University Of Eloued جامعة الوادي, 2023)
تركز هذه الدراسة على فهم ومعرفة العلاقة بين سمات الشخصية الخمس الكبرى ومعنى الحياة من جهة وسمات الشخصية الخمس الكبرى والتدفق النفسي من جهة أخرى لدى المصورين الفوتوغرافيين وكذلك تحديد الفروق بينهم بحسب الجنس وصفة المصور (حرفي وهاوي) ـ ولتحقيق هذا الهدف، تم تطبيق الدراسة على عينة قدرها 203 مصور فوتوغرافي وإستخدمت الباحثة مقياس سمات الشخصية الخمسة الكبرى (Goldberg 1999) ومقياس معنى الحياة (الأبيض 2010)، ومقياس التدفق النفسي (لأمل إباظه 2011) ـ واعتمدت على الأساليب الإحصائية التالية: اختبار كا2 اللابارامتري لحسن التطابق، اختبار"كا2" اللابارامتري للاستقلالية، اختبار كروكسال واليس(K.W.test) اللابارامتري، اختبار مان وتني" " لعينتين مستقلتين. وتوصلت الدراسة إلى النتائج التالية: - يوجد اختلاف دال احصائيا عند مستوى الدلالة ( ) بين سمات الشخصية لدى المصوّرين الفوتوغرافيين حسب العوامل الخمسة الكبرى للشخصية (Goldberg 1999) ـ - يتميز أغلبية المصوّرين الفوتوغرافيين بمستوى معنى الحياة منخفض ـ - يتميز أغلبية المصوّرين الفوتوغرافيين بمستوى تدفق نفسي منخفض ـ - الاختلاف في سمات الشخصية لدى المصوّرين الفوتوغرافيين لايؤدي إلى اختلاف دال احصائيا عند مستوى الدلالة ( ) في رتب درجات قياس معنى الحياة. - الاختلاف في سمات الشخصية لدى المصوّرين الفوتوغرافيين لا يؤدي إلى اختلاف دال احصائيا عند مستوى الدلالة ( ) في رتب درجات قياس التدفق النفسي. - لا يوجد اختلاف دال احصائيا عند مستوى الدلالة ( ) بين الذكور والاناث من المصوّرين الفوتوغرافيين على مقياس سمات الشخصية الخمس الكبرى (Goldberg, 1999). - يوجد اختلاف دال احصائيا عند مستوى الدلالة ( ) بين الحرفيين والهواة من المصوّرين الفوتوغرافيين على مقياس سمات الشخصية الخمس الكبرى (Goldberg 1999). - لا توجد فروق دالة احصائيا عند مستوى الدلالة ( ) بين الذكور والاناث من المصوّرين الفوتوغرافيين على مقياس معنى الحياة. - لا توجد فروق دالة احصائيا عند مستوى الدلالة ( ) بين الذكور والاناث من المصوّرين الفوتوغرافيين على مقياس التدفق النفسي. - لا توجد فروق دالة احصائيا عند مستوى الدلالة ( ) بين الحرفيين والهواة من المصوّرين الفوتوغرافيين على مقياس معنى الحياة. - لا توجد فروق دالة احصائيا عند مستوى الدلالة ( ) بين الحرفيين والهواة من المصوّرين الفوتوغرافيين على مقياس التدفق النفسي. Abstract: This study focuses on understanding and knowing the relationship between the big five personality traits and the meaning of life on the one hand, and the big five personality traits and psychological flow for photographers on the other hand. To achieve this goal, the study was applied to a sample of 203 photographers. As well as determining the differences between them according to gender and the state of the photographer (artisan and amateur), the researcher used the five major personality traits scale (Goldberg 1999), the meaning of life scale (Al-Abyad 2010), and the psychological flow scale (Amal Abaza 2011). It relied on the following statistical methods: the non-parametric Ca2 test for good congruence, the nonparametric "Ca2" test for independence, the nonparametric Croxall-Wallis (K.W.test) test, and the Mann-Whitney test for two independent samples. The study reached the following results: - There is a statistically significant difference at the level of significance ( ) between the big five personality traits of photographers according to the big five personality traits (Goldberg 1999) . -The majority of photographers have a low level of meaning in life. -Most photographers have a low level of psychological flow. - The difference in the big five personality traits of the photographers does not lead to a statistically significant difference at the level of significance ( ) in the ranks of the degrees of measuring the meaning of life. - The difference in the personality traits of the photographers does not lead to a statistically significant difference at the significance level ( ) in the ranks of the psychological flow measurement scores. -There is no statistically significant difference at the significance level ( ) between male and female photographers on the scale of the big five personality traits (Goldberg, 1999). -There is a statistically significant difference at the significance level ( ) between professional and amateur photographers on the scale of thebig five Personality traits (Goldberg 1999). -There are no statistically significant differences at the significance level ( ( between male and female photographers on the meaning of life scale. - There are no statistically significant differences at the significance level ( ) between male and female photographers on the psychological flow scale. - There are no statistically significant differences at the significance level ) between professional and amateur photographers on the meaning of life scale. - There are no statistically significant differences at the significance level( ) between professional and amateur photographers on the psychological flow scale.
(دراسة على بعض الجمعيات للتصوير في الجزائر
أطروحة
Keywords: سمات الشخصية الخمس الكبرى; معنى الحياة; التدفق النفسي; المصورين الفوتوغرافين; the big five personality traits; meaning of life; psychological flow; photographers